(untitled) (Comprehensive Journal of Science, 2025)
Libya is characterized by a relatively moderate climate in the north and a desert climate (hot and dry) in the south, where the desert climate areas are characterized by high temperatures and low rainfall rates in addition to the large change in temperatures between night and day, and due to the presence of many airports in these southern regions. It has aircraft parking areas and maintenance areas. Therefore, many problems appeared in the concrete paving at the construction joints in these areas, resulting in poor paving performance. This study aims to identify the causes and mechanisms of damage to concrete paving in airports located in hot, dry areas in Libya and to suggest treatment methods. And to know concrete paving and construction joints. This study included a field and reference study of airports located in hot climate areas, namely Ghadames, Sebha, airports, to identify all concrete pavements, construction joints between concrete pavements and asphalt shoulders, and the transition zone between concrete pavements and asphalt pavements, and to identify the prevailing and similar damages to concrete pavements at these airports. By analyzing the causes of damage, it became clear that most of them in concrete pavement are directly or indirectly related to the movement of concrete slabs. It was found that the damages were similar, namely the widening of the gaps between the concrete pavement and the asphalt shoulders, their filling with sand, and the elevation of the asphalt pavement above the level of the concrete pavement surface. The expansion joints widened by a distance of up to 5 cm and were filled with sand, as at Sebha Airport, and some contraction joints widened by a distance of up to 10 cm and were filled with sand, as a result of the thermal expansion of the concrete and the rise in temperatures. It became clear that the gap between the concrete and asphalt pavement at the end of the buried concrete slab widens during the shrinkage movement and is penetrated by sand. When the concrete pavement expands, the asphalt pavement rises upwards as a result of the concrete pavement pushing on it. The asphalt pavement collapses. Treatment methods were suggested using a camera to prevent movement transfer between the concrete and asphalt pavement, as well as paving a strip 1.5 to 2 meters wide with aggregate only, adjacent to the concrete pavement. Wide expansion joints are treated by removing the entire slab and re-pouring it. One of the conclusions of this study is that the failure of the designs did not take into account the environmental conditions at Ghadames Airport, such as the large change in temperatures, which caused excessive expansion and contraction, and thus an increase in the value of the coefficient of expansion of the concrete. This repeated thermal movement caused the expansion of the joints. When constructing concrete pavements in hot areas, it was recommended that the distance between expansion joints should not exceed 30 metres, that the reinforcement mesh should be continuous